2013
DOI: 10.1007/s10928-013-9302-8
|View full text |Cite
|
Sign up to set email alerts
|

Two general methods for population pharmacokinetic modeling: non-parametric adaptive grid and non-parametric Bayesian

Abstract: Population pharmacokinetic (PK) modeling methods can be statistically classified as either parametric or nonparametric (NP). Each classification can be divided into maximum likelihood (ML) or Bayesian (B) approazches. In this paper we discuss the nonparametric case using both maximum likelihood and Bayesian approaches. We present two nonparametric methods for estimating the unknown joint population distribution of model parameter values in a pharmacokinetic/pharmacodynamic (PK/PD) dataset. The first method is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 32 publications
0
61
0
2
Order By: Relevance
“…Within Pmetrics, we used the nonparametric adaptive grid (NPAG) algorithm (19,21,22) to build a population pharmacokinetic model for the pooled data sets, referred to here as the data set. On the basis of the prior work of numerous authors, as reviewed by Marsot et al (23), we used a two-compartment model for vancomycin, parameterized with linear elimination (K e ) from the central compartment with a volume (V c ) and linear transfer to (K CP ) and from (K PC ) the peripheral compartment.…”
Section: Methodsmentioning
confidence: 99%
“…Within Pmetrics, we used the nonparametric adaptive grid (NPAG) algorithm (19,21,22) to build a population pharmacokinetic model for the pooled data sets, referred to here as the data set. On the basis of the prior work of numerous authors, as reviewed by Marsot et al (23), we used a two-compartment model for vancomycin, parameterized with linear elimination (K e ) from the central compartment with a volume (V c ) and linear transfer to (K CP ) and from (K PC ) the peripheral compartment.…”
Section: Methodsmentioning
confidence: 99%
“…It was used to identify the best structural model and to perform the covariate analysis. The nonparametric adaptive grid (NPAG) algorithm implemented in Pmetrics software was used for the final analysis and simulation studies, because this program has shown its ability to identify outliers (24,25). The initial steps were performed with Monolix software to reduce the computation time.…”
Section: Methodsmentioning
confidence: 99%
“…One-and two-compartment models were developed with the nonparametric adaptive grid (NPAG) algorithm within the freely available Pmetrics software package for R (Laboratory of Applied Pharmacokinetics, University of Southern California, Los Angeles, CA) (20,21). Elimination from the central compartment and the intercompartmental distribution (two-compartment model) into the peripheral compartment were modeled as first-order processes.…”
Section: Patient Data Collectionmentioning
confidence: 99%